Community Welfare Perspective Islamic Human Development Index (IHDI) - Ahmad Yunadi; Syafiq Mahmadah Hanafi; Aziz Muslim (Al-Intaj)
Purpose: This study aims to analyze community welfare through the Islamic Human Development Index (IHDI) framework